1997
DOI: 10.1038/ki.1997.18
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL stimulates the expression of TGF-β and fibronectin in human glomerular epithelial cells

Abstract: Abnormal lipid accumulation in glomeruli is a recognized early event in the development of glomerulosclerosis. The presence of LDL and scavenger receptors has recently been demonstrated in glomerular cells, including the visceral epithelial cells. To explore the possible molecular mechanisms of lipid-induced glomerular injury, the present investigation was conducted to examine the effects of oxidized LDL (ox-LDL) on the expression of transforming growth factor (TGF)-beta and fibronectin by cultured human glome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…Moreover, Ox-LDL also promotes fibrosis by stimulating synthesis and expression of TGF-␤. 35 The redox-sensitive TGF-␤ regulates many fundamental biological processes and is a key mediator in chronic kidney disease. 36 We observed previously in early atherosclerosis increased tubular and glomerular TGF-␤ expression, 8 which could be manipulated by pharmacological intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ox-LDL also promotes fibrosis by stimulating synthesis and expression of TGF-␤. 35 The redox-sensitive TGF-␤ regulates many fundamental biological processes and is a key mediator in chronic kidney disease. 36 We observed previously in early atherosclerosis increased tubular and glomerular TGF-␤ expression, 8 which could be manipulated by pharmacological intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This hypercholesterolemia might be triggered by the enhancement of albumin and TC production in the liver, resulting from hypoalbuminemia (17). Furthermore, it has been reported that hypercholesterolemia is a factor that underlies the progression of renal injury, as well as being a risk factor for arteriosclerosis (18), because the deposition and oxidization of plasma cholesterol in glomeruli and tubules induces the expression of transforming growth factor-b1 and thus accelerates renal injury (19,20). In SHC rats, the abnormality of cholesterol metabolism appeared at the same time as the onset of albuminuria, and this hypercholesterolemia may contribute partially to the pathogenesis and progression of renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…9 In vitro studies have demonstrated that LDL and oxidized LDL stimulate TGF-β1 gene expression in both human glomerular mesangial and epithelial cells. 10,11 Therefore, TGF-β1 appears to be an important mediator of lipid-induced mesangial matrix expansion as well as playing a key role in the pathogenesis of diabetic nephropathy. 4,[10][11][12] Finally, the uptake of modified LDL by macrophages has been reported to stimulate eicosanoid synthesis including thromboxanes and leukotrienes, leading to potentially deleterious alterations in intra-glomerular hemodynamics.…”
Section: Mechanisms Of Lipid-induced Renal Injury In the Glomerulusmentioning
confidence: 99%
“…10,11 Therefore, TGF-β1 appears to be an important mediator of lipid-induced mesangial matrix expansion as well as playing a key role in the pathogenesis of diabetic nephropathy. 4,[10][11][12] Finally, the uptake of modified LDL by macrophages has been reported to stimulate eicosanoid synthesis including thromboxanes and leukotrienes, leading to potentially deleterious alterations in intra-glomerular hemodynamics. 6 In this regard, dietary cholesterol supplementation in animals has been shown to result in an increase in efferent arteriole resistance and a subsequent elevation in intra-glomerular pressure.…”
Section: Mechanisms Of Lipid-induced Renal Injury In the Glomerulusmentioning
confidence: 99%